Analisis Perbandingan Penggunaan Bekisting Bata dan Bekisting Konvensional pada Pembangunan Gedung Bertingkat - Dion Saputra Sune; Mohammad Yusuf Tuloli; Arfan Usman Sumaga (Transbahasa, 2025)
Formwork is a temporary construction, serves to give the shape of a reinforced concrete construction and as a concrete bearer until the construction is strong enough. During the construction process, it must be carefully considered what type of formwork will be used. The purpose of this study is to compare the cost and duration of using conventional formwork and brick formwork and analyze the type of formwork that is appropriate for use in multi-storey buildings. The method used is the interview method to the executor to obtain information about the formwork used during the work. Data analysis starts from calculating the total volume required for floor slab and beam work. The results of the comparison analysis of the cost of implementing conventional formwork work amounted to Rp. 205,465,979, and the cost of red brick formwork work amounted to Rp. 132,519,797. with a cost difference of Rp. 72,946,182. The results of the comparative analysis of the implementation duration for conventional formwork work require a duration of 45 days, and for red brick formwork work requires a duration of 18 days with a time difference of 27 days.